Antibiotic resistance patterns in municipal wastewater bacteria - Nagulapally, Sujatha Reddy (Kansas State University, 2007)
Antibiotics and pharmaceuticals are used to improve the quality of life worldwide. However, incomplete metabolism in humans has resulted in the release of large amounts of pharmaceutical drugs into municipal wastewater treatment plant. Past research has shown the release of antibiotic resistant organisms through wastewater effluents into streams and several studies have reported the occurrence of antibiotic resistant bacteria in major U.S. Rivers. Antibiotic resistant bacteria evolve and are selected by long-term environmental exposure to the low concentrations of antibiotics at the ng /L to g/L range. Infections caused by antibiotic resistant organisms are difficult to treat. The aim of this study was to analyze antibiotic resistance patterns in selected wastewater bacteria that include fecal coliforms, Escherichia coli and enterococci. Microorganisms in municipal wastewater treatment plant influent, secondary clarifier effluent and disinfected effluent were plated in the presence of predetermined concentrations of selected antibiotics. These antibiotics included ciprofloxacin, sulfamethoxazole/ trimethoprim and vancomycin. The diversity of enterococci was further investigated with PCR analysis. Fecal coliforms, E. coli and enterococci were found to be resistant or highly resistant to one or more target antibiotics in the influent and secondary clarifier (SC) effluent. Biological treatment reduced the number of overall and resistant bacteria in the SC effluent sample. UV disinfection was generally very effective and eliminated all fecal indicator organisms.
Keywords: Antibiotic Resistance; Bacteria; Municipal Wastewater; Engineering, Civil (0543); Engineering, Environmental (0775)